Identifying patient-centred recommendations for improving patient safety in General Practices in England: a qualitative content analysis of free-text responses using the Patient Reported Experiences and Outcomes of Safety in Primary Care (PREOS-PC) questionnaire - Ricci Cabello, Ignacio (2017)
There is a growing interest in identifying strategies to achieve safer primary health-care provision. However, most of the research conducted so far in this area relies on information supplied by health-care providers, and limited attention has been paid to patients’ perspectives. Objective: To explore patients’ experiences and perceptions of patient safety in English general practices with the aim of eliciting patient-centred recommendations for improving patient safety. Methods: The Patient Reported Experiences and Outcomes of Safety in Primary Care questionnaire was sent to a random sample of 6736 primary care users registered in 45 English practices. We conducted a qualitative content analysis of responses to seven open-ended items addressing patients’ experiences of safety problems, lessons learnt as a result of such experiences and recommendations for safer health care. Results: A total of 1244 (18.4%) participants returned completed questionnaires. Of those, 678 (54.5%) responded to at least one open-ended question. Two main themes emerged as follows: (i) experiences of safety problems and (ii) good practices and recommendations to improve patient safety in primary care. Most frequent experiences of safety problems were related to appointments, coordination between providers, tests, medication and diagnosis. Patients’ responses to these problems included increased patient activation (eg speaking up about concerns with their health care) and avoidance of unnecessary health care. Recommendations for safer health care included improvements in patient-centred communication, continuity of care, timely appointments, technical quality of care, active monitoring, teamwork, health records and practice environment. Conclusion: This study identified a number of patient-centred recommendations for improving patient safety in English general practices.